Analysis of the Influence Of Scientific Writing Course on English Writing Ability - Andriyani, Kiki; Gandari, Meisy; Nurcholis, Ivan Achmad (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine how much influence the scientific writing course has on the ability to write English sentences in semester 6 students of the English Language Education Study Program, University of Muhammadiyah Bengkulu. Where as we know that writing activities in their function as productive skills are still considered difficult by students. Things like this are usually caused by several factors such as limited knowledge of vocabulary and a lack of understanding of English grammar. These factors are the main cause of the difficulty for students to develop ideas and write English sentences properly and correctly. Therefore, one of the methods used to overcome this problem is to practice writing a lot, one of which is in scientific writing courses.